Degradable and biocompatible hydrogels bearing a hindered urea bond. (25th October 2017) - Ying, Hanze; Yen, Jonathan; Wang, Ruibo; Lai, Yang; Hsu, Jer-Luen-Aaron; Hu, Yuhang; Cheng, Jianjun
Abstract : Polymers containing hindered urea bonds are novel platforms for designing degradable hydrogels suitable for protein release and stem cell encapsulation. Abstract : A hindered urea bond (HUB), recently reported as a new type of dynamic chemical bond, can be facilely constructed by mixing an isocyanate and a hindered amine. Here, we report the use of the HUB in the design of degradable hydrogel materials for applications of stem cell encapsulation and delivery. Polyethyleneglycol (PEG) diamine was end-capped with a HUB and an allyl group in a one-pot synthesis. The resulting polymer was cross-linked to form a hydrogel under UV with the addition of a 4-arm PEG thiol and a photoinitiator. The degradation properties of the hydrogels were confirmed with NMR, GPC, weight loss, and protein release studies. We found that the degradation kinetics is dependent on the size of the N -substituents, and the one with the tert -butyl group shows complete degradation within 2 days. The new hydrogel materials were also demonstrated to be biocompatible with hMSCs, and the cell release kinetics can be facilely tuned over 5 days.